Prevalensi Nyeri Tenggorok Pascaoperasi dengan Pemberian Lubrikasi VCO pada Pemasangan LMA - Rahmadhya Khairina Rianti; Dedy Kurnia; Afdal Afdal (Fakultas Kedokteran, Universitas Andalas, 2020)
Background. Postoperative sore throat (POST) is a common complication after general anaesthesia. It affects patient satisfaction and can affect activity after discharge. The supraglottic airway device (SAD) offers an alternative to traditional tracheal intubation with potential benefit in preventing sore throat. Numerous agents have been used as lubricant to reduce the incidence of POST with variable efficacy. The purpose of this study is to determine the prevalence of postoperative sore throat in patients with Virgin Coconut Oil (VCO) as a lubricant for Laryngeal Mask Airway (LMA) insertion in patients undergoing general anaesthesia for elective surgery. Objective. Determine the prevalence of postoperative sore throat in patients by giving Virgin Coconut Oil (VCO) as a lubricant for the Laryngeal Mask Airway (LMA) installation under general anesthesia for elective surgery. Methods. This is an observational descriptive study, was conducted in December 2019 until June 2020 at Surgical Installation RSUP dr. M. Djamil Padang and Andalas University Hospital. Forty-two subjects were recruited to this study taken by using consecutive sampling technique. Results. Patients evaluated about sore throat at immediately, 2 hours, and 24 hours post-operative period. POST was observed in 47,6% of the patients in immediate post-operative period. After 2 hours 23,8% patients had sore-throat, and after 24 hours 9,5% patients had sore-throat. Among patients had sore throat after 24 hours, the intensity was mild. Conclusion. We conclude that lubricating cuff of LMA with VCO can reduce the prevalence of POST. Keyword: Laryngeal Mask Airway, sore throat, Virgin Coconut Oil